THU0143 Vascular wall inflamation in rheumatoid arthritis patients decreases after 6 months of anti-inflammatory therapy with methotrexate or adalimumab as measured by 18f-fdg-pet/ct. (12th June 2018) - Blanken, A.; Agca, R.; Voskuijl, A.; Boellaard, R.; van der Laken, C.; Nurmohamed, M.
Abstract : Background: Patients with rheumatoid arthritis (RA) have an elevated cardiovascular (CV) disease risk, mostly explained by both an increased prevalence of traditional CV risk factors and the presence of systemic inflammation that accelerates atherosclerosis. There is accumulating evidence that anti-inflammatory treatment for RA reduces this CV risk. A non-invasive tool for detecting vascular wall inflammation in atherosclerosis is 18F-Fluorodeoxyglucose-Positron Emission Tomography/Computed Tomography (18F-FDG-PET/CT). Objectives: To study the effect of anti-inflammatory treatment with methotrexate (MTX) or adalimumab on vascular wall inflammation in RA assessed by 18F-FDG-PET/CT. Methods: 18F-FDG-PET/CT was done in patients with active early RA starting MTX (n=25) and active established RA starting adalimumab (n=24) before and after 6 months of therapy, and in osteoarthritis controls (OA; n=29). 18F-FDG uptake in arterial wall was determined by standardised uptake values (SUV). Volumes of interest covering the arterial segment with the highest 18F-FDG were defined to derive the maximum SUV (SUVmax) in the ascending, descending and abdominal aorta and the aortic arch. Global arterial uptake was estimated using the mean SUVmax of the four arterial segments. Results: Mean age was 65±9 for early RA, 61±7 for established RA and 63±5 years for OA controls. Median disease duration was 2.1 (interquartile range (IQR) 1.3–3.3) weeks for early RA and 6.9 (IQR 1.8–13.9) years for established RA. DAS28 was 4.9±1.0 and 4.4±1.0 at baseline and declined to 3.1±1.3 and 2.8±1.4 after 6 months therapy, respectively. At baseline mean SUVmax was 1.86±0.38 for early RA, 1.68±0.43 for established RA and 1.56±0.41 for OA controles. SUVmax tended to decline more in early RA patients when compared to established RA (1.86±0.38 to 1.79±0.43 (-3.7%) and 1.68±0.43 to 1.63±0.43 (-3.0%), respectively). SUVmax in most arterial segments declined after 6 months of therapy (table 1). The most prominent decline in SUVmax was in de abdominal aorta in established RA patients (−9.8%). Conclusions: A decline in global arterial SUVmax and in most of arterial segments was found in both early and established RA patients after 6 months of MTX and/or adalimumab, suggesting that anti-inflammatory therapy with either MTX and/or adalimumab decreases arterial wall inflammation and thus CV risk in RA. Disclosure of Interest: None declared